Arvonlisäveron vaikutus maatilan talouteen - Marjamaa, Seija; Puurunen, Maija (Maatalouden taloudellinen tutkimuslaitos, 1996)
The study examines the impact of value added tax on farm economy by the means of book-keeping results of the agricultural profitability study concerning milk and grain farms as well as piggeries specialised in piglet and pork production.The economic situation in 1995 was estimated on the basis of returns and costs in 1993 and the impact of value added tax on farms income. The analysis conserns only agriculture; the share of forestry has been taken into account only if it is closely associated with of agriculture. The study also examines the value added tax on the macro level. The examination bases on the returns and costs of agricultural total accounting made by the Agricultural Economic Research Institute.
Keywords: Ma; arvonlisävero; maataloustulo; accounting; value added tax; farm income